Interval oscillation criteria for second order nonlinear differential equations with damping - Rogovchenko, Yuri V.; Tuncay, Fatos (Dynamic Publishers, Inc, 2007)
Using generalized Riccati transformations, for a second order nonlinear differential equation with a damping term we derive nontrivial extensions of oscillation criteria obtained for linear equations by Kong [J. Math. Anal. Appl. 229 (1999), 258-270]. Efficiency of new results is illustrated on the example extracted from the recent paper by Sun [J. Math. Anal. Appl. 291 (2004), 341-351].
Keywords: Theorems